Gender equity in university students in Mexico City, after 20 months of remote classes during the COVID-19 pandemic - Saldívar-Garduño, Alicia; Alarcón-Aguilar, Adriana; Cervantes-Ríos, Elsa; López-Diazguerrero, Norma Edith; Gómez-González, Beatriz; Gaitán-González, Mercedes Jatziri; Konigsberg, Mina (Frontiers in Education, 2024)
Several studies have reported that university students were affected during the months of confinement due to the COVID-19 pandemic. In Mexico, public and private universities were the last to resume face-to-face activities, so the students stayed in remote classes for almost 20 months. Because of gender inequities in higher education, it is essential to analyze the differential effects of remote learning on male and female students in terms of their physical and mental health, motivation, school achievement, and students' adaptation to changes.Here we surveyed 573 students from Universidad Autónoma Metropolitana, Campus Iztapalapa in Mexico City, using a self-administration survey online. Our results showed that female students had more work overload at home, and felt more affected in their physical and mental health compared to men. Despite these difficulties, women were more willing to get ahead in academic and work settings.